2022
DOI: 10.22541/au.165829868.85398488/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-based Outcomes after Surgery for Acute Type A Aortic Dissection

Abstract: Background: While prior data have suggested worse outcomes in women after acute type A aortic dissection (ATAAD) repair when compared to men, results have been inconsistent across studies over time. This study sought to evaluate the impact of sex on short- and long-term outcomes after ATAAD repair. Methods: This was a retrospective study utilizing an institutional database of ATAAD repairs from 2007 to 2021. Patients were stratified according to sex. Kaplan-Meier survival estimation and multivariable Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Sex‐based outcomes following repair of acute type A aortic dissection (ATAAD) has been of considerable interest among researchers and the study by Yousef et al is another attempt to establish the impact of gender on outcomes 1 . The authors have examined a large institutional database over a 15‐year period and concluded that while there are differences in presentation, mortality is essentially similar between males and females.…”
mentioning
confidence: 99%
“…Sex‐based outcomes following repair of acute type A aortic dissection (ATAAD) has been of considerable interest among researchers and the study by Yousef et al is another attempt to establish the impact of gender on outcomes 1 . The authors have examined a large institutional database over a 15‐year period and concluded that while there are differences in presentation, mortality is essentially similar between males and females.…”
mentioning
confidence: 99%